Power and Light Plant - Frank Aston::::::photographer:::
West elevation, garden in the foreground. 1902-04 Biennial Report notes a Power House designed by Weeks; similarity in design/construction of roofs of Main Bldgs. and Weeks Powerhouse v. roof on 'New' Power House; location of the older/newer Power Houses in relation to Main Bldgs., evident in maps and plans of campus.